DEKADENSI KEPEMIMPINAN DAN DISINTEGRASI TUBUH KRISTUS: ANALISIS TEOLOGI ETIS TERHADAP KRISIS MORALITAS GEREJA DI ERA KONTEMPORER - Wahju Astjarjo Rini (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Church leadership today is facing a serious crisis due to the weakening of moral integrity and the increasing prevalence of ethical banality. Many cases show that authoritarian behaviour, abuse of power, desire for position and power, and immoral behaviour have created deep wounds in the faith community and damaged the integrity of the Body of Christ. This phenomenon is a strong indicator of the decline of leadership that no longer stands on biblical values and ethical theological principles that should be the foundation of Christian ministry. The disintegration of the church as a direct result of moral failure in leadership highlights the urgency of re-examining the relationship between Christian ethics and power structures within the church. This study aims to analyse theologically and ethically how leadership decadence contributes to church division in the contemporary era. Using a qualitative approach with a literature review method, it can be concluded that amoral and banal leadership in Christianity is the primary factor causing moral decadence, leading to the disintegration of the Body of Christ and a crisis of church morality. When leadership loses its spiritual dimension and ethical integrity, the church is no longer able to carry out its prophetic function in society. Therefore, leadership actualisation and reform strategies that emphasise moral education and accountability are needed as efforts to restore spiritual authority and church unity.